Trends and priorities in occupational health research and knowledge transfer in Italy - Bruna Maria Rondinone; Fabio Boccuni; Sergio Iavicoli (Nordic Association of Occupational Safety and Health (NOROSH), 2010)
OBJECTIVES: In 2000-2001, the Italian National Institute for Occupational Safety and Prevention (ISPESL) carried out a survey to identify the research priorities in the field of occupational safety and health (OSH). The present study, carried out in 2007-2008, was a follow-up designed to (i) review the themes identified earlier, (ii) detect emerging issues linked to new risks and forms of work, and (iii) look for any shifts in focus. The survey was extended to cover not only research but also the concept of knowledge transfer. METHODS: In the first round, ISPESL distributed questionnaires to the heads of both university occupational medicine departments and prevention departments in local national health units (known as ASL in Italy) asking respondents to identify OSH priority themes. In the latest survey covering both research and the need for knowledge transfer, the same experts were asked to rank the importance of the earlier-identified topics and list any emerging issues in the OSH field. RESULTS: The two most important themes identified were "work accidents" and "occupational carcinogenesis". In the overall sample and among ASL experts, they received the 1st and 2nd highest mean scores. The university respondents also prioritized them but in reverse order. Some of the new priority topics included: risks associated with nanotechnologies; assessment of psychosocial and organizational risks; migration and work; and cost-benefit analysis of prevention. CONCLUSION: In light of the findings, efforts are urgently needed to identify research and knowledge transfer priorities related to workers' health and safety on an international scale using a standardized method in order to obtain comparable results, avoid wasteful duplication of resources, and reduce occupational accidents and illness.